Prevention and health promotion for the excluded and the destitute in Europe - Chauvin, Pierre (Biomedical and health research, 2002)
The social inequalities of health have persisted, or even increased, in Europe in the last few years. This text presents the experiences of professionals from various institutional backgrounds in eight European countries, as well as their recommendations to improve the access of excluded people.